Socioeconomic status of the elderly MS population compared to the general population: a nationwide Danish matched cross-sectional study - Wandall-Holm, Malthe Faurschou; Holm, Rolf Pringler; Pontieri, Luigi; Sellebjerg, Finn; Magyari, Melinda (Frontiers in Neurology, 2023)
Introduction/objectives Multiple sclerosis (MS) leads to physical and cognitive disability, which in turn impacts the socioeconomic status of the individual. The altered socioeconomic trajectory combined with the critical role of aging in MS progression could potentially lead to pronounced differences between MS patients and the general population. Few nations have the ability to connect long-term clinical and socioeconomic data at the individual level, and Denmark's robust population-based registries offer unique insights. This study aimed to examine the socioeconomic aspects of elderly Danish MS patients in comparison to matched controls from the general population. Methods A nationwide population-based study in Denmark was conducted, comprising all living MS patients aged 50 years or older as of 1 January 2021. Patients were matched 1:10 based on sex, age, ethnicity, and residence with a 25% sample of the total Danish population. Demographic and clinical information was sourced from the Danish Multiple Sclerosis Registry, while socioeconomic data were derived from national population-based registries containing details on education, employment, social services, and household characteristics. Univariate comparisons between MS patients and matched controls were then carried out. Results The study included 8,215 MS patients and 82,150 matched individuals, with a mean age of 63.4 years (SD: 8.9) and a 2:1 female-to-male ratio. For those aged 50–64 years, MS patients demonstrated lower educational attainment (high education: 28.3 vs. 34.4%, P < 0.001) and fewer received income from employment (46.0 vs. 78.9%, P < 0.001), and working individuals had a lower annual income (48,500 vs. 53,500€, P < 0.001) in comparison to the controls. Additionally, MS patients within this age group were more likely to receive publicly funded practical assistance (14.3 vs. 1.6%, P < 0.001) and personal care (10.5 vs. 0.8%, P < 0.001). Across the entire population, MS patients were more likely to live alone (38.7 vs. 33.8%, P < 0.001) and less likely to have one or more children (84.2 vs. 87.0%, P < 0.001). Conclusion MS presents significant socioeconomic challenges among the elderly population, such as unemployment, reduced income, and increased dependence on social care. These findings underscore the pervasive impact of MS on an individual's life course, extending beyond the clinical symptoms of cognitive and physical impairment.